Actualization of Al-Ma’un Theology in Muhammadiyah Governance in Lamongan Regency: A Study of Civil Society in Enhancing Community Welfare - ., Shodikin; Supriyono, Bambang; Muluk, M. R. Khairul; Rozikin, Mochammad (Journal of Posthumanism, 2025)
This study aims to critically examine the actualization of Al-Ma’un theology in the organizational governance of Muhammadiyah in Lamongan Regency, particularly in its role as a civil society actor in promoting community welfare. Employing a qualitative approach within an interpretive paradigm, the research focuses on how the core values of Al-Ma’un—such as compassion for the poor, orphans, and marginalized groups—are internalized and implemented through Muhammadiyah’s local-level institutional policies, programs, and practices. Data were collected through in-depth interviews, participatory observation, and document analysis of Muhammadiyah’s philanthropic ventures in education, health, social services, and economic empowerment. The findings reveal that Muhammadiyah in Lamongan has successfully grounded Al-Ma’un theology in its governance system, characterized by accountability, transparency, participation, and a strong orientation toward community empowerment. Al-Ma’un theology functions not only as a spiritual foundation but also as a praxis-oriented paradigm that drives social transformation and inclusive development rooted in Islamic values. The study affirms that modernist Islamic movements like Muhammadiyah can serve as effective agents of social change by integrating theological principles into institutional frameworks and public service delivery. Moreover, the research proposes a governance model based on Al-Ma’un theology that can be replicated to enhance the role of civil society in achieving the Sustainable Development Goals (SDGs). This study contributes conceptually to the discourse on public administration grounded in Islamic ethics and values.